(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Scheduled Castes and Scheduled Tribes (Prevention of Atrocities Act, 1989 is to protect the people from the weaker section of society. This special law is to protect the people from the atrocities. But this special law cannot be used for setting settling and scoring personal vendetta or by way some counter blasts against opponents some public servants. Court cannot deny the right of anticipatory bail on merely technical grounds.